Atrial fibrillation after heart transplantation - M. Kh. Lepshokova; E. D. Kosmachova; V. A. Porkhanov (Трансплантология (Москва))
Arrhythmias in heart transplant recipients remain an important but under-studied issue in transplant medicine. One of the most common arrhythmias, atrial fibrillation can cause cardioembolic complications in transplant recipients, in the same way as in general population and, accordingly, affect the quality of life and the prognosis. This review discusses epidemiology, classification, mechanisms of development, and therapy of atrial fibrillation after heart transplantation.